SYSTEMATIC REVIEW OF THE EFFICIENCY OF TELEMEDICINE DURING THE COVID-19 PANDEMIC - Yuniasih, Dewi; Mansur, Auliya Azisah; Dewantari, Aulia Nissa; Dewantari, Aulia Yasmin; Annisa, Ika Nur; Susilawati, Okti (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
COVID-19 is a world health problem that has caused significant changes in the health care system. During the COVID-19 pandemic, some efforts are needed to reduce the spread of the. Telemedicine, as a remote technology, is one of the effective options for use in the healthcare system today. This study aims to explore the efficiency of using telemedicine as one of the facilities in the context of controlling COVID-19. This systematic review research uses 4 databases: PubMed, ScienceDirect, ProQuest, and Wiley. The keywords used are "telemedicine" or "telehealth," "e-Health," and "COVID-19". The inclusion criteria are the articles that contain telemedicine in the control of COVID-19, published in 2021 in Indonesian or English by accredited journals, and using observational, descriptive, or case research. About 1,877 article titles were identified, and 1,869 were excluded because they were irrelevant and did not match the inclusion factor. A total of 8 articles were included in the analysis of this study. One article found that the effectiveness of telemedicine for rural communities is difficult to access. Six articles found that telemedicine reduces the frequency of visits to doctors/hospitals, reduces transportation costs, reduces hospitalization time and costs, reduces the workload of health workers, and reduces the transmission of COVID-19. One article listed the effectiveness of telemedicine for COPD patients with COVID-19. Telemedicine as a health care system is a promising effort during the COVID-19 pandemic and has excellent potential to help reduce the burden of health costs.